The Amethyst Kingdom - Mulford, A. K. (HarperCollins Publishers, 2024)
The fifth and final novel in the Five Crowns of Okrith romantasy series. A young fae warrior is hellbent on winning the Eastern Court crown, but when her fated lover–and hated nemesis–Ersan enters the trials she struggles to balance the competition and the chance at love. The crown is calling her name, but can her head bear the weight when passion sets her heart racing?
Description based on publisher supplied metadata and other sources
Keywords: Witches; Magic; Kings and rulers; Contests; Inheritance and succession; Swords; Imaginary wars and battles; Blessing and cursing; Magic - Fiction; Sorcières - Romans; nouvelles; etc; Rois et souverains - Romans; nouvelles; etc; Concours et compétitions - Romans; nouvelles; etc; Successions et héritages - Romans; nouvelles; etc; Guerres et batailles imaginaires - Romans; nouvelles; etc; Bénédiction et malédiction - Romans; nouvelles; etc; Fantasy fiction; Romance fiction